Influência do selamento dentinário imediato na polimerização de materiais de moldagem e na resistência à fratura de coroa em cerâmica - Ghiggi, Paula Cristine (2013)
The first section of this study evaluated the interaction between resin materials used in the immediate dentin sealing (IDS) techniques and impression materials under two different techniques to reduce/eliminate the oxygen-inhibition layer. The occlusal dentin of 35 human molars was exposed and finished with 400 grit silicon carbide sandpaper. Teeth were randomly divided into 2 groups: group 1 impression with vinyl polysiloxane Express XT, group 2 impression with polyether Impregum. Groups 1 and 2 were divided into 14 subgroups: groups 1a e 2a: control groups; groups 1b e 2b: IDS with Clearfil SE Bond (CSE); groups 1c e 2c: IDS with CSE + additional polymerization with glycerine jelly; groups 1d e 2d: IDS with CSE + alcohol; groups 1e e 2e: IDS with CSE and Protect Liner F (PLF); groups 1f e 2f: IDS with CSE and PLF + additional polymerization with glycerin jelly; groups 1g e 2g: IDS with CSE and PLF + alcohol. Each tooth surface was photographed using a digital camera. The images saved were used to examine the presence of impression material left on the treated tooth surface. It was observed that IDS performed with CSE or with the PLF interacted with the Express XT and with the Impregum. The application of glycerine jelly and alcohol avoided the interaction of CSE with the Express XT and of the PLF with the Impregum; however, these treatments were not totally effective to avoid the interaction of CSE with the Impregum and of PLF with the Express XT. The second section of this study evaluate, in vitro, the thickness of the adhesive, low-viscosity microfilled resin, and resin cement on full crown preparations, and its effect on the fracture load of a reinforced all-ceramic crown. Sixty maxillary premolars received full crown preparation and were divided in 3 groups according to the material applied for the immediate dentin sealing: G1 control; G2 CSE Bond; G3 CSE Bond + PLF. After taking the impression with polyvinyl siloxane, the preparations were temporized with acrylic resin crowns. IPS Empress 2 restorations were fabricated, and cemented to the preparations with Panavia F. Ten specimens of each group were submitted to fracture load testing, and the other 10 specimens were sectioned buccolingually, and the thicknesses of Panavia F, CSE Bond and PLF were measured in 10 different positions using a microscope. According to ANOVA and Tukey s test, the fracture load of group 3 (1300 N) was statistically higher than group 1 (1001 N) (p<0.01). Group 2 (1189 N) was not statistically different from groups 1 and 3. The higher thickness of the CSE Bond was obtained in the concave part of the preparation. The PLF presented a more uniform range of values at different positions. The thickness of Panavia F was higher in the occlusal portion of the preparation. The film thickness formed by CSE Bond and PLF increased the fracture load of the IPS Empress 2 ceramic crown.